Pelestarian Kearifan Lokal Tari Tradisional Dalam Upaya Meningkatkan Keterampilan Seni - Rohmattuloh; Dwiyan Nur Santosa; Bagas Yoga Pratama (STAI AL-AMIN, 2024)
Local wisdom is a cultural heritage that reflects the identity and noble values of a society. One form of local wisdom that has an important role in preserving culture is traditional dance. Preserving traditional dance in an educational context, especially in elementary schools, is very important to instill a love of local culture from an early age and improve students' artistic skills. The method used in this research is a descriptive qualitative method, this method was chosen because the problem being studied concerns things that are going on in the school. in this case, it is about